Review of 43 spider species from Hainan Island, China (Arachnida, Araneae) - Lin, Yejie; Wu, Lingbing; Cai, Ducheng; Li, Shuqiang; Barrion, Alberto Tomas; Heong, Kong Luen (Magnolia Press, 2023)
Photographs of the type specimens of nine spider species described by Barrion et al. (2013) from Hainan Island, China, considered as valid taxa in this study, are provided. Among them, three new combinations are proposed: Clubiona pandalira (Barrion-Dupo, Barrion & Heong, 2013) comb. nov. (ex Nusatidia Deeleman-Reinhold, 2001); Dictis edwardsi (Barrion, Barrion-Dupo & Heong, 2013) comb. nov. (ex Scytodes Latreille, 1804); and Nesioneta mingshengzhui (Barrion, Barrion-Dupo & Heong, 2013) comb. nov. (ex Meioneta Hull, 1920). Thirty-one new synonyms are proposed and three species are considered as nomina dubia.